SISTEM PENCARIAN RUTE DISTRIBUSI TERPENDEK MENGGUNAKAN ALGORITMA GENETIKA (STUDI KASUS DISTRIBUTOR SARI ROTI YOGYAKARTA) - adena reis vanrika (JMAI (Jurnal Multimedia & Artificial Intelligence), 2020)
In the modern era is the role of technology is very useful and rapidly evolved in societies, technology can make efficient and make effective activity or employment in the community, one of the roles of the current technology has been widely used in by the community i.e. google maps, google maps itself many uses and benefits of its one that is looking for a location to various places and then showing the route of the journey. On the existence of a travel distribution company couriers to deliver its products to any location of the consumer. These problems in the case of travelling salesmen problem (TSP), where a courier will visit a number of n points. and every point should only be visited once in addition to the starting point. In this study, researchers aim to create a system that can locate the most minimum distribution route using a genetic algorithm, utilizing the features of google maps so that the impact on the effectiveness of time and transportation costs. Genetic algorithm is a heuristic algorithm is used to resolve the problem by way of mengoptimasikan the problem with imitating the process of evolution of living beings. In this study data on use is data from the distributor sari bread jogjakarta. Data on testing trainers in this research aims to find the best algorithm parameter values and parameter values that is obtained by the total population = 100, maximum = 100 genes, the crossover rate = 0.5, and the mutation rate is 0.1. Of the 5 test data, by performing a test on each of the 10 test data. then the obtained results of genetic algorithm performance results percentage of 84% of the route or the value of an optimal fitness, and 16% showed error route that is not optimal.